(untitled) (International Journal of Nursing Education, 2026)
Objective: Historically, nursing students have found bioscience subjects challenging and anxiety provoking. To alleviate these factors, an online industry-based short course, Biochemical Basis for Human Life (BBHL) was developed. A survey with narrative analysis was used to explore learners’ experience and satisfaction with the course and evaluate the effectiveness of microlearning approach in delivering nursing bioscience education. Methods: Learners enrolled in the short course and following the course completion, they were invited to submit the End of Course Feedback survey. The survey included quantitative measures of course satisfaction, demographics pertaining to learners’ country of origin and two open ended qualitative questions. Results: A total of 444 learners were enrolled in the course, with 33.3% completion rate (148/444). Out of the learners who completed the course, 89.9% (133/148) completed the End of Course Feedback survey. Across all questions, agreement rates exceeded 90%, with negligible disagreement or nonresponse in relation to course satisfaction. Out of the learners who provided a qualitative response, majority expressed positive attitudes towards course delivery and course impact. Conclusions: This study highlighted the beneficial nature of the course and its microlearning approach in relation to nursing bioscience education. Furthermore, this study provides a new strategy for educators where a bite-sized learning can be used as pre-classroom preparation for students to enhance student engagement and decrease burden associated with extensive material coverage in the classroom.